Efficient terahertz devices based on III–V semiconductor photoconductors. Issue 2 (1st April 2014) - Kostakis, Ioannis; Saeedkia, Daryoosh; Missous, Mohamed
Abstract : A series of planar aperture and dipole antenna structures fabricated on low temperature grown GaAs and InP‐based photoconductors have been evaluated as terahertz (THz) emitters and detectors in a time‐domain spectroscopy system under pulsed excitation. The combination of large aperture antennas as emitters and short dipole antennas as detectors results in efficient THz devices operating at 800 nm, 1 μm and 1.55 μm excitation wavelengths. The system responses of these materials are among the best ever reported and allow high‐quality measurements to be made. Finally, characterisation of a structure able to be biased vertically and its evaluation as THz emitter is reported for the first time. The THz response of this material with a strong THz signal at low‐voltage bias makes the development of battery‐operated THz devices possible.